Erratum to: Fermionic UV models for neutral triple gauge boson vertices - Ricardo Cepedello; Fabian Esser; Martin Hirsch; Veronica Sanz (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP07(2024)275